Cu2O-HTM/SiO2-ETM assisted for synthesis engineering improving efficiency and stability with heterojunction planar perovskite thin-film solar cells. (1st July 2020) - Tseng, Chzu-Chiang; Chen, Lung-Chien; Chang, Liann-Be; Wu, Gwo-Mei; Feng, Wu-Shiung; Jeng, Ming-Jer; Chen, Dave W.; Lee, Kuan-Lin
Highlights: A perovskite solar cell with Cu2 O/MAPbI3 /SiO2 heterojunction structure is studied. A novel synthesized engineering with thinly Cu2 O HTML and ultra-thin SiO2 ETML has developed. Cu2 O HTML and SiO2 ETML could improve PCE and carrier charge for recombination and recollection, which leads to an impactful enhancement in open-circuit voltage (Voc). The stable Voc effect was induced by constructing the interfilm of Cu2 O and SiO2 between the CH3 NH3 PbI3 active layer, resulting in an excellent PCE of 18.4%. Abstract: Perovskite solar cells (PSCs) have been made eligible for proficient power conversion efficiency (PCE) by optimizing the perovskite film's morphology, formation, interfaces, and charge collection for increased effectiveness. This paper applied a new method for Cu2 O/methylammonium lead iodide (MAPbI3 )/SiO2 structure with heterojunction PSCs. This paper developed a novel synthesis engineering method for thin Cu2 O hole-transporting material layer (HTML) and ultrathin SiO2 electron-transporting material layer (ETML). Cu2 O HTML and SiO2 ETML could improve the PCE and carrier charge for recombination and recollection. The architecture includes a reduced film thickness by hetero-contact synthesis engineering, which resulted in an impactful enhancement of open-circuit voltage (Voc). The stable Voc effect was induced by constructing the interfilm of Cu2 O and SiO2 between the main CH3 NH3 PbI3 layers, which transported electrons/electron holes, resulting in an excellent PCE of 18.4%. The fabrication showed that inorganic materials can be applied for the potential interfacial engineering of perovskite-based solar cells.